Parking prices and availability, mode choice and urban form - Sofia F. Franco (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2020)
This paper provides evidence how parking reforms can help reduce car dependency and achieve a more efficient use of city space. It looks at how the price and availability of parking influence transport choices and urban form. It also investigates the effect of minimum parking requirements and regulations on developer decisions and land use. The paper draws primarily on evidence from Los Angeles County and the City of Los Angeles, California, in the United States.
Keywords: 330; Parken; Verwaltungskosten; Räumliche Wirkung; Verkehrspolitik; Los Angeles (Calif.; County)